Bringing satellites down to Earth: Six steps to more ethical remote sensing - Mia M. Bennett; Colin J. Gleason; Beth Tellman; Luis F. Alvarez Leon; Hannah K. Friedrich; Ufuoma Ovienmhada; Adam J. Mathews (Global Environmental Change Advances, 2024)
To shed light on the politics of remote sensing, a technique often regarded as objective and neutral, the subfield of critical remote sensing has emerged in the social sciences. This perspective translates its key ideas into an actionable framework that offers suggestions for how to transform remote sensing to better engage and empower people and places typically studied at a distance. First, we encourage remote sensing scientists and practitioners to weigh the consequences of exposing inaccessible or off-limits places, incorporate local knowledge and values into research design, methods, and applications, and share skills and data with stakeholders who wish to learn and use remote sensing for their own objectives. Second, we offer suggestions for teaching critical remote sensing and making research accessible and replicable. Third, we stress the importance of acknowledging that despite being conducted from afar, remote sensing can still affect the people and places it observes.